Formação continuada de professores alfabetizadores: um estudo do PNAIC no município de Crato/CE - Silva, Vanusa Daniel da (2018)
This dissertation aims to analyze the National Pact for Literacy in the Right Age (PNAIC) and the implications for the pedagogical work of literacy teachers. Initially, the paper presents a brief analysis of the history of teacher education in Brazil, in order to understand the reasons that led to the precariousness of the initial and continuing education policies of Basic Education teachers. Next, we discuss the relationship between the state and public policies in capitalist society by placing education as a disputed field, and then enter into educational policy studies that have supported the elaboration of the pact in the local context. From the methodological point of view, it is a quantitative / qualitative, documentary and exploratory research in the dialectical perspective. The data collection instruments, we used questionnaires and semi-structured interviews with nine teachers who work in the literacy cycle in four schools in the city of Crato/CE. Through this study, it was possible to affirm that even bringing contributions to the pedagogical practice of the teacher, the continued formation in the PNAIC has not developed in a satisfactory way, due to the precarious conditions in which the municipal schools are. Thus, instead of promoting the professional development of literacy teachers, it has implications for pedagogical work such as emptying theory and denying teaching. In this sense, this study points to the need to review the program in its structure considering the reality of the empirical field, in the perspective of thinking about the formation that enables the professional development of the teacher and overcoming the precariousness of the teaching work.